Fasting and sports: a summary statement of the IOC workshop - Maughan, R. J.; Al-Kharusi, W.; Binnett, M. S.; Budgett, R.; Burke, L. M.; Coyle, E. F.; Elwani, R.; Guezennec, C. Y.; Limna, J.; Mujika, I.; Ramadan, J.; Schamasch, P.; et al. (British Journal of Sports Medicine, 2012)
Fasting—the abstention from eating and drinking—is an integral part of all of the world's major cultures and religions, though the pattern of fasting and the rate of adherence both vary widely. Fasting is also practised by many individuals in the belief that health benefits will result. A fast may be total or partial and may be prolonged or intermittent: it may be practised at prescribed times of the year for a fixed duration or at the discretion of the individual.